1991
DOI: 10.1177/009102609102000406
|View full text |Cite
|
Sign up to set email alerts
|

MPA Graduates and the Dilemma of Job Satisfaction: Does Crossing the Sector Line Make a Difference

Abstract: This study examines levels of job satisfaction for MPA graduates employed in the public, private, and non-profit sectors. Findings are based on a survey and indicate that MPA graduates derive greater satisfaction with pay and promotion opportunities in the private sector than in the public or non-profit sectors. No significant differences were noted between the sectors with regard to work satisfaction or satisfaction with supervisor or co-workers. Further, no differences in levels of satisfaction were noted be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Often we find job satisfaction studies that compare private sector and public sector employees (Blunt & Spring, 1991;Bogg & Cooper, 1995;Gabris & Simo, 1995;Maidani, 1991;Rainey, 1989;Steel & Warner, 1990) based on the assumptions that the public sector employee differs from his or her private sector counterpart and that the public sector work environment differs from the private sector work environment. Unfortunately, while differences in job satisfaction often appear to exist between sectors, there is no consistency in those results across the literature.…”
Section: What Has Been the Focus Of Other Researchers?mentioning
confidence: 99%
“…Often we find job satisfaction studies that compare private sector and public sector employees (Blunt & Spring, 1991;Bogg & Cooper, 1995;Gabris & Simo, 1995;Maidani, 1991;Rainey, 1989;Steel & Warner, 1990) based on the assumptions that the public sector employee differs from his or her private sector counterpart and that the public sector work environment differs from the private sector work environment. Unfortunately, while differences in job satisfaction often appear to exist between sectors, there is no consistency in those results across the literature.…”
Section: What Has Been the Focus Of Other Researchers?mentioning
confidence: 99%
“…Furthermore, it helps augment extant literature examining models and determinants of job satisfaction for employees, specifically those in nonprofit organizations. This literature has consistently found that although much of what we know about job satisfaction collected in for-profit organizations extends to nonprofits (for example, Blunt and Spring, 1991;Ronen, 1977), there are some differences. For example, perceptions of the agency's mission take on increased importance for understanding employee job satisfaction in nonprofit organizations (Brown and Yoshioka, 2003).…”
Section: Employee Experiences With Volunteersmentioning
confidence: 99%
“…Yet other scholars find no differences in self-reported work ethic of public and private sector employees. [7,10,18,21,33] The mixed evidence probably stems from the self-reporting methodology, and if so, managerial perceptions should tap into the underlying intrinsic value of public service that motivates a stronger work ethic. Therefore, public and nonprofit managers should be less concerned about work ethic than the public sector as specified below.…”
Section: The Push and Pull Of Sectoral Differencesmentioning
confidence: 99%
“…All establishments in the 9200 series of NAICS and all public elementary and secondary schools (typically coded as 6111) are considered public sector organizations. Nonprofit organizations are more difficult to categorize, but Blunt and Spring [33] demonstrate the use of SIC codes to identify establishments that tended toward hybrid characterizations and are largely organized as nonprofits. Translating SIC codes to NAICS codes suggests that establishments categorized as 5191, 6112-6115, 6232, 6239, 6241-6244, 7121, and 8139 closely approximates the nonprofit sector.…”
Section: Explanatory and Control Variablesmentioning
confidence: 99%